2012
DOI: 10.1371/journal.pone.0040107
|View full text |Cite
|
Sign up to set email alerts
|

Common Variants on Chromosome 9p21 Are Associated with Normal Tension Glaucoma

Abstract: Although intraocular pressure (IOP) is the most definitive cause of glaucoma, a subtype of open angle glaucoma (OAG) termed normal tension glaucoma (NTG), which occurs in spite of normal IOP, accounts for a large part of glaucoma cases, especially in Japan. To find common genetic variants contributing to NTG in Japanese patients, we conducted a genome-wide association study (GWAS). We performed the first screening for 531,009 autosomal SNPs with a discovery cohort of 286 cases and 557 controls, and then a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 83 publications
8
51
1
1
Order By: Relevance
“…Recently, several POAG susceptibility loci were identified by genome-wide association (GWA) studies [16][17][18][19][20] and were replicated in multiple ethnicities: 7q31.2 between CAV1 and CAV2, 16,21 9p21.3 with CDKN2B-AS1, 19,20,[22][23][24][25][26] 10q21.3 with ATOH7, 17,18,22,27 and 14q23.1 between SIX1 and SIX6. 17,20,22,28 One of the GWA studies demonstrated the association of POAG with six SNPs that flanked the ZP4, PLXDC2, and TMTC2 genes located at chromosome loci 1q43, 10p12.31, and 12q21.31, respectively, in a Japanese population; 29 however, these associations were not replicated in a South Indian, 30 Afro-Caribbean, 24 or Chinese 31 population.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several POAG susceptibility loci were identified by genome-wide association (GWA) studies [16][17][18][19][20] and were replicated in multiple ethnicities: 7q31.2 between CAV1 and CAV2, 16,21 9p21.3 with CDKN2B-AS1, 19,20,[22][23][24][25][26] 10q21.3 with ATOH7, 17,18,22,27 and 14q23.1 between SIX1 and SIX6. 17,20,22,28 One of the GWA studies demonstrated the association of POAG with six SNPs that flanked the ZP4, PLXDC2, and TMTC2 genes located at chromosome loci 1q43, 10p12.31, and 12q21.31, respectively, in a Japanese population; 29 however, these associations were not replicated in a South Indian, 30 Afro-Caribbean, 24 or Chinese 31 population.…”
Section: Introductionmentioning
confidence: 99%
“…The most significant region to be identified, by independent research groups, as having an association with POAG in different population samples is the CDKN2B-AS1 region on chromosome 9p21 [7], [8], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20]. The significance of this finding derives from the fact that SNPs which affect genetic expression in the region of CDKN2B-AS1 are known to be associated with a number of diseases such as coronary heart disease [21], [22], [23], types 1 and 2 diabetes [21], [24], [25], atherosclerosis [26] and different cancers (see reviews by Pasmant et al ., 2011 and Cunnington et al ., 2010 [24], [25]).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, they investigated the Japan Nakano et al (2009) extent of the involvement of these loci in glaucoma and found an association between the variants in CDKN2B, ATOH7, and SIX1 and glaucoma . Subsequent GWASs confirmed the association of these genetic variants with POAG in different ethnic groups (Khor et al, 2011;Nakano et al, 2012;Osman et al, 2012;Ozel et al, 2014;Takamoto et al, 2012). It has been reported that CDKN2B and ATOH are more strongly associated with NTG compared to HTG Mabuchi et al, 2012;Nakano et al, 2012;Wiggs et al, 2012).…”
Section: Association Studies For Poagmentioning
confidence: 86%